Development Of A Liquid Phase Microextraction Technique For The Gas Chromatographic Determination Of Fatty Acids In Vegetable Oils - Gan, Hui Siang (2012)
This thesis is focused on the development of a two phase hollow fiber liquid-phase microextraction technique, followed by gas-chromatography-flame ionization detection (GC-FID) for the profiling of the fatty acids (FAs) (lauric, myristic, palmitic, stearic, palmitoleic, oleic, linoleic, linolenic and arachidic) in vegetable oils. Heptadecanoic acid methyl ester was used as the internal standard. The FAs were transesterified by a two step method to their corresponding methyl esters prior to the extraction. Extraction parameters such as type of extracting solvent, temperature, extraction time, stirring speed and salt addition were studied and optimized. Recommended conditions were: extraction solvent, n-tridecane; extraction time, 35 min; stirring rate, 1700 rpm; extraction temperature, ambient; without addition of salt. The analytes were extracted from 10 mL donor phase through 5 μL of an organic solvent immobilized in the pores of a porous polypropylene hollow fiber and then into the acceptor phase present inside the hollow fiber. Enrichment factors varying from 37 to 115 were achieved. Calibration curves for the nine FAs were well correlated (r2 > 0.994) within the range of 10–5000 μg L−1. The limit of detection (signal: noise, 3) was 4.73 – 13.21 ng L−1. The results presented show that the hollow fiber liquid-phase microextraction techniques can serve as excellent alternative methods to conventional sample preparation techniques or other microextraction in the analysis of FAs. The method was successfully applied to the profiling of the FAs in palm oils (crude, olein, kernel, carotino cooking oil) and other vegetable oils (soybean, olive, coconut, rice bran and pumpkin). The encouraging enrichments achieved offer an interesting option for the profiling of the minor and major FAs in palm and other vegetable oils.